Nanotechnology for removal of personal care products and related compounds - Balakuntahalli Sakappa, Ramya Kumari; Mulla, Sikandar I.; Faniband, Basheerabegum; Golgeri M., Dilshad Begum; Ferreira, Luiz Fernando Romanholo; Rahdar, Abbas; Bhargava, Ram Naresh; Américo-Pinheiro, Juliana Heloisa Pinê [UNESP]; Bankole, Paul Olusegun (Elsevier, 2024)
In the current scenario, the pharmaceuticals and personal care items (PPCPs), including cosmetics and toiletries, cause pollution in various water bodies. In fact, it was found that extremely small amounts of these chemicals have negative effects on the environmental surroundings especially on living organisms. To understand the level of such problem(s), around the world, numerous research investigations have been conducted and reported on occurrence, effects, destiny, and removal processes of pharmaceutical compounds, personal care products (cosmetics and toiletries), natural water (all type water including lake, river, and sea), and wastewater produced by industries. The accidental existence of such useful chemicals (PPCPs) in various aquatic streams at lower concentrations capable of damaging aquatic creatures have observed more and more since last two decades. This has become a significant problem towards various organisms due to widespread and expanding use of PPCPs by human and also in veterinary medicine which eventually releases these chemicals into the environment. Hence, some of these chemicals listed as priority contaminants by the European Union and the US Environmental Protection Agency. Different research group have made a strategy to tackle this kind of problem. Here, this chapter discusses toxic effect and their removal using different methods. The chapter will provide information which is helpful to environmental engineering streams.
Keywords: algae; nanoparticles; PPCPs; removal; wastewater